Chlorophyll fluorescence, ion uptake, and osmoregulation are potential indicators for detecting ecotypic variation in salt tolerance of Panicum antidotale Retz*. Issue 1 (2nd January 2022) - Javed, Muhammad; Ashraf, Muhammad; Iqbal, Muhammad; Farooq, Muhammad Ahsan; Zafar, Zafar Ullah; Athar, Habib-ur-Rehman
Abstract: Efficient selection for salt tolerance using the choice of physiological traits is of great importance. In the present study, seven ecotypes of Panicum antidotale (four from the Cholistan Desert and three from the non-Cholistani area) were evaluated after three weeks of salt stress. Results showed that shoot fresh biomass decreased by 74 and 83% respectively in Cholistani, and non-Cholistani ecotypes under salt-stressed conditions compared to control. Ecotypes from the Cholistan were more salt-tolerant (average dry biomass, 4.02 g) than non-Cholistani ones (average dry biomass, 3.14 g). Averaged across the Cholistani and non-Cholistani ecotypes, Cholistani ecotypes accumulated lower Na + (72%) and/or higher K + (179%) concentrations in their leaves than non-Cholistani ecotypes. However, parallels between the degree of salt sensitivity and relative water content, leaf water potential, leaf osmotic potential, and leaf turgor potential could not be generalized. In Cholistani ecotypes under salt stress, the total soluble protein on average was higher (11.51%) compared to non-Cholistani ecotypes (8.5%). Chlorophyll a decreased (0–20%) in all populations due to salt stress and it was positively associated with solar energy absorption and electron transport but could not be used to discriminate the populations. Chlorophyll fluorescence data indicated that salt stress damaged PSII functionality and electron transport further than QA − . The effective quantum yield of PSII, performance index, antenna size, energy flux for electron transport, rate of PSII reaction center closure positively correlated with salt tolerance of P. antidotale .